2020
DOI: 10.1177/1355819620913141
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of accountable care organizations on patient experience, health outcomes and costs: a rapid review

Abstract: Objectives Accountable care organizations were implemented as a system-level approach to address quality differences and curb increasing healthcare costs in the United States of America, and have garnered the interest of policy makers in other countries to support better management of patients. The objectives of this paper are to: (1) identify the impacts of accountable care organizations on improving the quadruple aim goals of improving patient experience of care, enhancing population health outcomes, reducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 12 publications
0
18
0
4
Order By: Relevance
“…ACO-Verträge sind in als Anreiz an Leistungserbringer zu verstehen, Versorgungsnetzwerke zu gründen, in denen sie gemeinsam die Verantwortung für Versorgungskosten und -qualität einer definierten Population übernehmen. Diese Netzwerke erhalten dabei den Anreiz Versorgungskosten zu reduzieren, in dem sie einen Anteil an den für Medicare entstehenden Einsparungen rückvergütet erhalten [6]. Durch diese Verlagerung sollten bei mindestens gleichbleibender Qualität der Kostenanstieg von Medicare verlangsamt werden [7,8].…”
Section: Introductionunclassified
“…ACO-Verträge sind in als Anreiz an Leistungserbringer zu verstehen, Versorgungsnetzwerke zu gründen, in denen sie gemeinsam die Verantwortung für Versorgungskosten und -qualität einer definierten Population übernehmen. Diese Netzwerke erhalten dabei den Anreiz Versorgungskosten zu reduzieren, in dem sie einen Anteil an den für Medicare entstehenden Einsparungen rückvergütet erhalten [6]. Durch diese Verlagerung sollten bei mindestens gleichbleibender Qualität der Kostenanstieg von Medicare verlangsamt werden [7,8].…”
Section: Introductionunclassified
“…We are unaware of information on the effect of Accountable Care Organizations (ACOs) or other alternative payment models on the demand for care, physician incomes, or physician location, and the scant available information on provider experience suggests that it may be mixed. 34 ACO penetration grew considerably between 2010 and 2019, but the rate of growth was slightly higher in the first half of this period, preceding implementation of the ACA, compared with the second half. 35 Moreover, ACOs are present in every state, and our analysis of data presented in Muhlestein et al 35 indicates that penetration differs only slightly between expansion and nonexpansion states (Online Appendix H, Supplemental Digital Content 1, http://links.lww.com/MLR/C193 ).…”
Section: Discussionmentioning
confidence: 92%
“…9 A 2020 review found little evidence on ACOs and clinician experience. 8 Shared savings coming to an ACO may go to hospitals, specialists, and ancillary services, rather than to primary care. ACO savings are unlikely to improve primary care spend.…”
Section: Acomentioning
confidence: 99%